ANALISIS KEANEKARAGAMAN JENIS MANGROVE DI DESA MATABUBU JAYA KECAMATAN LAINEA KABUPATEN KONAWE SELATAN: Analysis of Species Diversity of Mangroves in Matabubu Jaya Village, Lainea District, South Konawe Regency - abdul sakti (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2025)
Mangrove forests are forests that grow in brackish water areas and are influenced by tidal fluctuations, with anaerobic soil conditions. These forests are commonly found in coastal areas filled with mud and abundant organic matter accumulation. This study aims to determine the species diversity of mangroves in Matabubu Jaya Village, Lainea District. The study population covers an area of 30.23 hectares, using a sampling intensity of 10%, resulting in a sample area of 3.02 hectares. Data collection was conducted using a transect method with plot sizes of 400 m², with a total of 75 plots. The research variables include relative density, relative frequency, relative dominance, the Important Value Index (IVI), and species diversity index using the Shannon-Wiener method. The analysis found 13 species of mangroves at the tree and pole levels, while 11 species were found at the stake level. At the tree level, Rhizophora apiculata had the highest IVI value of 58.29, at the pole level, Bruguiera gymnorrhiza had an IVI of 41.49, and at the stake level, Rhizophora stylosa had the highest IVI of 63.45. The species diversity index for the tree level was 0.49, categorized as low abundance, for the pole level was 0.52, categorized as low abundance, and for the stake level was 0.53, also categorized as low abundance.